STRATEGY IMPLEMENTATION: THE EFECT OF DECENTRALIZATION, PARTICIPATION IN BUDGET SETTING, AND MANAGERS’ ATTITUDE ON PERFORMANCE - Bambang Riyanto (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
The performance of a business unit, to a large extent, is determined by the quality of its strategy and how well the strategy is implemented. This study examines the effect ofstrategy implementation on performance. In particular, it investigates the extent to which the fit between two crucial strategic supporting systems, namely decentralization andbudget system, and managers’ attitude with the strategy of SBU on performance. It is argued that the more consistent the level of decentralization, degree of participation in thebudget system and managers’ attitude with the SBU strategies, the higher the performance will be, and vice versa. Unlike most prior studies, the hypothesis was tested by adopting the system of fit approach. Responses from 75 divisional managers of 75 diversified companies are analyzed. The results show that managers pursuing a strategy of differentiation (cost leadership) report high performance when they worked in highly (less) decentralized structures, are given more (less) opportunity to participate in the budget process, and had strongly positive attitude toward their jobs and their firms. These findings are consistent with the basic premise of strategy implementation that different strategies should be supported with different configuration of organizational structure and process to achieve optimal results.Keywords: strategy implementation, decentralization, participation, attitude, system of fit.